Simulating a European recovery fund - Friedrich Heinemann (ZEW - Leibniz Centre for European Economic Research, 2020)
European leaders debate the establishment of a "European Recovery Fund" (ERF). The ERF shall help the European economy to restart growth after the COVID-19 pandemic-related recession that is currently unfolding. Early national and European fiscal measures of anti-crisis policy have been focused on helping companies and employees to get throughthe immediate lockdown phase. The ERF targets at the second crisis phase that begins once the lockdowns are over.
Keywords: 330